Diverse strains of Actinobacillus lignieresii isolated from clinically affected cattle in a geographically restricted area. Issue 11 (1st September 2019) - Turni, C; Yee, S; Epstein, V; Jackson, B; Li, K; Knowles, G; Blackall, PJ
Abstract : Objective: To investigate whether an outbreak of Actinobacillus lignieresii was caused by one or multiple strains. Methods: Nine isolates of A. lignieresii were obtained from the lymph nodes of 15 affected cattle from two farms to determine whether a single strain was involved. An enterobacterial repetitive insertion consensus sequence (ERIC) PCR was used for genotyping, and the repeats‐in‐toxin genes were analysed by PCR and sequencing. Results: Isolates from the two farms belonged to two and three genotypes, with a total of four genotypes detected. Genes of the apxICABD operons of some strains had deletions in the apxIA (~697 bp) and in the apxID (~187 bp) genes. The toxin gene deletions and the ERIC PCR patterns suggested the involvement of different A. lignieresii genotypes. Conclusion: There was no evidence that a unique genotype was associated with actinobacillosis on the two farms, confirming that this disease was associated with other contributing factors.